Improving firm performance through Competitive Advantage, differentiation strategy and cost leadership: A Literature Review - Suprihono Suprihono; Arik Prasetya; Yusri Abdillah (Universitas Dharma Wacana, 2022)
This study aims to examine previous research in order to determine the role of competitive advantage as a variable that mediates the effect of differentiation strategy and cost leadership strategy on firm performance. This study applies various theories, namely resource-based-view (RBV) theory, and Market-based-view (MBV) theory to explain the relationship between variables. As a literature study article, this article contributes to developing a conceptual framework on how to combine the two perspectives of generic strategy and competitive different advantages. This article has importance for management and further research considering that not many previous studies have used the theoretical framework to test similar research models. This study has limitations in obtaining research that examines competitive advantage in research with firm performance. This research introduces a new framework that illustrates the contribution of competitive advantage to company performance through the implementation of a differentiation strategy and cost leadership strategy.